Phenotypic Alteration of a Human BK (hSlo) Channel byhSloβ Subunit Coexpression: Changes in Blocker Sensitivity, Activation/Relaxation and Inactivation Kinetics, and Protein Kinase A Modulation - Dworetzky, Steven I. (J Neurosci, 1996)
A human homolog of the large-conductance calcium-activated potassium (BK) channel β subunit (hSloβ) was cloned, and its effects on a human BK channel (hSlo) phenotype are reported. Coexpression of hSlo and hSloβ, in both oocytes and human embryonic kidney 293 cells, resulted in increased Ca(2+) sensitivity, marked slowing of BK channel activation and relaxation, and a significant reduction in slow inactivation. In addition, coexpression changed the pharmacology of the BK channel phenotype: hSlo-mediated currents in oocytes were more sensitive to the peptide toxin iberiotoxin than werehSlo + hSloβ currents, and the potency of blockade by the alkaloid BK blocker tetrandrine was much greater onhSlo + hSloβ-mediated currents compared withhSlo currents alone. No significant differences in the response to charybdotoxin or the BK channel opener NS1619 were observed. Modulation of BK channel activity by phosphorylation was also affected by the presence of the hSloβ subunit. Application of cAMP-dependent protein kinase increasedP(OPEN) of hSlo channels, but decreased P(OPEN) of most hSlo + hSloβ channels. Taken together, these altered characteristics may explain some of the wide diversity of BK channel phenotypes observed in native tissues.